(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
Despite the efforts made to develop and adapt the outputs of higher education to the requirements of the labor market and the needs of the society and improve it to achieve the desired goals. Despite the large increase in the number of universities, the low levels of graduates and the lack of adaptation to the requirements of the market and the needs of the community for many reasons, the productive and general economic situation of the country is unable to absorb the large numbers of graduates and the lack of planning from the concerned authorities to accommodate the large numbers of graduates. The problem of unemployment and the employment of the national workforce is one of the most important issues with social, economic and political implications in Iraq. An important explanation for the unemployment problem is the inadequacy of higher education outputs for labor market needs, In addition to identify some indicators of higher education in Iraq for future planning on realistic grounds.